2014
DOI: 10.1186/1756-0500-7-287
|View full text |Cite
|
Sign up to set email alerts
|

Complete steady-state rate equation for DNA ligase and its use for measuring product kinetic parameters of NAD+-dependent DNA ligase from Haemophilus influenzae

Abstract: BackgroundDNA ligase seals the nicks in the phosphodiester backbone between Okazaki fragments during DNA replication. DNA ligase has an unusual Bi Ter Ping Pong kinetic mechanism. Its substrates in eubacteria are NAD+ and nicked DNA (nDNA). Its products are nicotinamide mononucleotide (NMN), adenosine 5′-monophosphate (AMP), and sealed DNA. Investigation of the kinetic mechanism and measurement of the kinetic constants of DNA ligase using steady-state kinetics would benefit from the availability of the complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…To our knowledge, this is the first transient state kinetic analysis of a LigA–AMP enzyme. Our finding adds to existing steady-state kinetic studies of the NAD + -dependent nick joining reactions of Eco LigA and Haemophilus influenzae LigA, both of which are stimulated strongly by ammonium sulfate ( 37 , 52 , 53 ). We found that ammonium ion enhances the rate of step 2 and step 3 catalysis by Eco LigA–AMP, as much as 53-fold and 20-fold, respectively, at 15 mM ammonium sulfate.…”
Section: Discussionsupporting
confidence: 58%
“…To our knowledge, this is the first transient state kinetic analysis of a LigA–AMP enzyme. Our finding adds to existing steady-state kinetic studies of the NAD + -dependent nick joining reactions of Eco LigA and Haemophilus influenzae LigA, both of which are stimulated strongly by ammonium sulfate ( 37 , 52 , 53 ). We found that ammonium ion enhances the rate of step 2 and step 3 catalysis by Eco LigA–AMP, as much as 53-fold and 20-fold, respectively, at 15 mM ammonium sulfate.…”
Section: Discussionsupporting
confidence: 58%
“…[ 36 ] In all cases, the inhibition equilibrium constant (K i ) of the 75mer-ds-nDNA substrate was estimated to be 200–500 nM for these ligases. In addition to uncompetitive substrate inhibition, the inhibition could also potentially be explained by a competitive model, with nicked substrate binding to deadenylylated ligase inhibiting the self-adenylylation reaction through blocking binding of ATP [ 6 , 37 ]. Thus, the T4 substrate inhibition data was also fit with a competitive substrate inhibition model for an ordered Bi-Bi Ping-Pong mechanism ( Eq 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…[ 6 , 37 ] For these enzymes, it was hypothesized that the underlying mechanistic reason for the inhibition was the competitive binding of deadenylylated enzyme to the nicked substrate, thus inhibiting enzyme self-adenylylation. [ 6 , 37 ] In this study, EMSAs performed with a deadenylylated form of T4 DNA ligase clearly demonstrated that stable binding of nicked DNA does occur for this ligase ( Fig 4 ), providing direct evidence for potential inhibition of enzyme self-adenylylation through this mechanism. An important corollary to this substrate inhibition mechanistic hypothesis is that the studies of H .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of biophysical chemistry approaches have been used to detect the joining of DNA strand breaks. Those applied to NDLs or ADLs from bacteria or archaea include use of fluorescently-labelled probes [ 66 , 70 , 72 , 73 ], FRET [ 69 , 74 77 ], fluorescence quenching and molecular beacon-based approaches [ 78 81 ], electrochemical methods [ 67 , 79 , 81 84 ], a nanoparticle-based sensor [ 85 ] and surface plasmon resonance [ 86 ]. Biochemical analyses of the ligation reaction are facilitated by assays that do not require ‘labelling’ of the nucleic acid, such as label-free electrochemical approaches using mercury-based electrodes and nicked plasmid DNA substrates [ 67 ].…”
Section: Assays Of Dna Joining By Dna Ligasesmentioning
confidence: 99%